(untitled) - Robertson, Suzanne (Upper Saddle River, NJ, 2006)
Volere Requirements Process Model; project blastoff; determining requirements; user and stakeholders; project constraints; requirements constraints; use cases; business events; adjacent systems; innovation; trawling for requirements: apprenticing, interviews, and videotape; functional and nonfunctional requirements; fit criteria; quality gateways; traceability; prototyping and scenarios; low and high fidelity prototypes; patterns and requirements reuse; improving the requirements gathering process.
Keywords: Project management,Quản lý đề án